EKSTRAKSI DAN KARAKTERISASI GELATIN TULANG KAMBING KACANG MENGGUNAKAN NEUTRASE - Dellen N. Matulessy; Yuni Erwanto; Nurliani Nurliani; Edy Suryanto (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
This study aims was to evaluate the characteristics of the gelatine derivate from Kacang goat bone extracted enzymatically using neutrase at different enzyme concentrations. The neutrase treatments, namely GTK-N0 (gelatin with neutrase 0%), GTK-N1 (Gelatin with 0.25% neutrase), GTK-N2 (Gelatin with neutrase 0.5%) and GTK-N3 (Gelatin with neutrase 0,75%). The bones sample used the bones from local Kacang goat aged 6 to 12 months. The study used was a randomized complete design (Oneway ANOVA) with 4 enzyme concentration treatments with 5 replications each treatment. The parameters observed were gelatin yields, the proximate analysis was performed on goat bones and gelatin (water content, ash, fat, and crude protein), pH, gel strength, viscosity, and functional groups of gelatin FTIR. The results showed that the application of the neutrase enzyme at the 0.25% level had the significant effect on the characteristics of the gelatin produced. The conclusion of this study neutrase can be used for enzymatically extracting gelatin from the bones of local Kacang goat and produced the gelatin characteristics that can be used for food applications.